The Efficacy and Use of a Pocket Card Algorithm in Status Epilepticus Treatment. Issue 5 (October 2021) - Fesler, Jessica R.; Belcher, Anne E.; Moosa, Ahsan N.; Mays, MaryAnn; Jehi, Lara E.; Pestana Knight, Elia M.; Lachhwani, Deepak K.; Alexopoulos, Andreas V.; Nair, Dileep R.; Punia, Vineet
Abstract : Objective: To determine whether a pocket card treatment algorithm improves the early treatment of status epilepticus and to assess its utilization and retention in clinical practice. Methods: Multidisciplinary care teams participated in video-recorded status epilepticus simulation sessions from 2015 to 2019. In this longitudinal cohort study, we examined the sessions recorded before and after introducing an internally developed, guideline-derived pocket card to determine differences in the adequacy or timeliness of rescue benzodiazepine. Simulation participants were queried 9 months later for submission of a differentiating identification number on each card to assess ongoing availability and utilization. Results: Forty-four teams were included (22 before and 22 after the introduction of the pocket card). The time to rescue therapy was shorter for teams with the pocket card available (84 seconds [64–132]) compared with teams before introduction (144 seconds [100–162]) (U = 94; median difference = −46.9, 95% confidence interval [CI]: −75.9 to −21.9). The adequate dosing did not differ with card availability (odds ratio 1.48, 95% CI: 0.43–5.1). At the 9-month follow-up, 32 participants (65%) completed the survey, with 26 (81%) self-reporting having the pocket card available and 11 (34%) confirming ready access with the identification number. All identification numbers submitted corresponded to the hard copy laminated pocket card, and none to the electronic version. Conclusions: A pocket card is a feasible, effective, and worthwhile educational tool to improve the implementation of updated guidelines for the treatment of status epilepticus.